THE PASSWORD IS ... (New York Times, 2023)
The article focuses on the early days of computer hacking in 1992 and the methods used by hackers to obtain passwords and cause mischief. Topics include skilled hackers breaking into national computer networks, stealing passwords by rummaging through trash bins for technical manuals, and the increasing prevalence of hacking as society relied more on powerful computer networks.